DisCrit Classroom Ecology: Using praxis to dismantle dysfunctional education ecologies. (July 2018) - Annamma, Subini; Morrison, Deb
Abstract: Using a critical conceptual analysis, we theorize a DisCrit Classroom Ecology to counter current dysfunctional education ecologies. We begin by exploring the lineage of Critical Race Theory, through both its intellectual forerunner Gift Theory and a more recent sibling, DisCrit. Next, we explore the three interrelated constructs of DisCrit Classroom Ecology; Pedagogy, Curriculum, and Solidarity, and the strand that animates them, DisCrit Resistance. Finally, we discuss the deep implications and transformative possibilities of using praxis to (re)organize classrooms through a DisCrit Classroom Ecology. Highlights: Education is a system of dysfunctional education landscapes for Students of Color. Framed in Disability Critical Race Theory, we conceptualized DisCrit Classroom Ecology. We explore the constructs of DisCrit Curriculum, Pedagogy, and Solidarity. Using praxis, each construct is animated through a DisCrit Resistance. Implications change the focus of the classroom and thus, pedagogical practice.